Modern Food Safety and Product Identification - Füzesi, István (Acta Agraria Debreceniensis, 2005)
In the beginning of the 21st century the matter of food safety plays an accentuated role in the food industry. Important issues in this topic are the risk of bioterrorism, impurities in the food chain and the ascendancy of customer needs. The solutions of these problems are the introduction of modern quality assurance systems, traceability and identification of products. I review in this paper the possibilities of these systems, the potential advantages and incidental costs. In the tight frame of this paper – omitting the descriptions of technologies – I discuss the most important criterions of systems, which may be able to solve today’s quality food industry problems.